Early screening for preeclampsia Rastreamento precoce da pré-eclampsia - Fabrício da Silva Costa; Padma Murthi; Rosemary Keogh; Nicole Woodrow (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2011)
Preeclampsia, which affects about 3 to 5% of pregnant women, is the most frequent medical complication in pregnancy and the most important cause of maternal and perinatal morbidity and mortality. During the past three decades, numerous clinical, biophysical, and biochemical screening tests have been proposed for the early detection of preeclampsia. Literature shows large discrepancies in the sensitivity and predictive value of several of these tests. No single screening test used for preeclampsia prediction has gained widespread acceptance into clinical practice. Instead, its value seems to be in increasing the predictive value of panels of tests, which include other clinical measurements. The aim of this review was to examine the combination of maternal risk factors, mean arterial blood pressure, and uterine artery Doppler, together with biomarkers in the preeclampsia prediction. A pré-eclâmpsia, que afeta cerca de 3 a 5% das mulheres grávidas, é a mais frequente complicação médica durante a gestação e a mais importante causa de morbidade e mortalidade maternal e perinatal. Durante as últimas três décadas, numerosos testes de rastreamento clínicos, biofísicos e bioquímicos foram propostos para a detecção precoce da pré-eclâmpsia. A literatura mostra grandes discrepâncias na sensibilidade e no valor preditivo de muitos desses testes. Nenhum teste de rastreamento isolado usado para a predição da pré-eclâmpsia tem ganhado ampla aceitação na prática clínica. Ao contrário, parece que o valor preditivo aumenta com a inclusão de um painel de testes, os quais incluem outros parâmetros clínicos. O objetivo desta revisão foi examinar a combinação dos fatores de risco maternos, a pressão arterial média, o Doppler das artérias uterinas com os marcadores séricos, na predição da pré-eclâmpsia.